COMPUTER SELF-EFFICACY, AUDITOR EXPERIENCE, AND AUDITOR COMPETENCE ON AUDIT QUALITY WITH THE USE OF ATLAS APPLICATION AS A MODERATION - Hapsara, Made Yoga; Suwarno, Try Edi; Yuniarta, Gede Adi; Purnamawati, I Gusti Ayu (JURNAL INFORMASI, PERPAJAKAN, AKUNTANSI, DAN KEUANGAN PUBLIK, 2025)
This research aims to determine and prove empirically the significance of the influence of computer self-efficiency, auditor experience, and auditor competence on audit quality which is moderated by the use of the ATLAS application. The population that is the object of this study consists of 86 auditors working at KAP in Bali. This research uses a purposive sampling method with auditor criteria of auditors who are willing to take the time to fill out the questionnaire and return it. From these criteria, 14 auditors were unwilling to fill out and return the questionnaire, so the sample studied was 72 questionnaires. Data collection was carried out by distributing questionnaires and documentation to each respondent. The data was then analyzed using the SEM PLS statistical application. The results of partial hypothesis research show that computer self-efficiency does not affect audit quality, In contrast, auditor experience and auditor competence have a positive and significant impact on audit quality. Meanwhile, the ATLAS application does not moderate the influence of computer self-efficiency, auditor experience, and auditor competency on audit quality.